2007
DOI: 10.1007/s11010-007-9486-6
|View full text |Cite
|
Sign up to set email alerts
|

Probucol modulates iron nitrilotriacetate (Fe-NTA)-dependent renal carcinogenesis and hyperproliferative response: diminution of oxidative stress

Abstract: Probucol is a clinically used cholesterol-lowering drug, with pronounced antioxidant properties. We have reported previously, that dietary supplementation of probucol enhances NAD(P)H:quinone reductase (Iqbal M, Okada S (2003) Pharmacol Toxicol 93:259-263) and inhibits Fe-NTA induced lipid peroxidation and DNA damage in vitro (Iqbal M, Sharma SD, Oakada (2004) Redox Rep 9:167-172). Further to this, in the present study, we evaluated the modulatory effect of probucol on iron nitrilotriacetae (Fe-NTA) dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In animals, probucol prevents intimal thickening after balloon injury, independent of its ability to lower cholesterol and inhibit lipoprotein lipid oxidation [14] . Probucol is reported to exert antitumor activities at various stages of tumor initiation, promotion and progression [15] . However, these findings do not explain the roles of probucol in AMPK activation and cell growth in glioma.…”
Section: Introductionmentioning
confidence: 99%
“…In animals, probucol prevents intimal thickening after balloon injury, independent of its ability to lower cholesterol and inhibit lipoprotein lipid oxidation [14] . Probucol is reported to exert antitumor activities at various stages of tumor initiation, promotion and progression [15] . However, these findings do not explain the roles of probucol in AMPK activation and cell growth in glioma.…”
Section: Introductionmentioning
confidence: 99%
“…In one of these studies, directed nanoassembly formulation of probucol was tested and it was shown to suppress lung metastasis of breast cancer 24 and in another study it inhibited benzopyrene induced lung tumorigenesis 25 .In addition, probucol was reported to induce antiproliferative effects via inhibition of cell cycle progression and inactivation of NF-κB and MAPK pathways in human ovarian cancer cells 26 . Probucol was also reported to exert chemopreventive effect in kidney cancer 27 and probucol treatment of KB cells xenografts in mice had a significant anticancer effect by anti-angiogenic and apoptosis inducing mechanisms 28 . In our knowledge, this is the first study investigating the effects of probucol on K562S, K562R chronic myeloid leukemia, U266, H929 and RPMI8226 multipl myeloma and L929 fibroblast cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been demonstrated that human diet contains many antimutagens and antioxidants. These compounds have been reported to play a significant role in the inhibition of the initiation and the promotion of some cancer [ 20 ]. Recently, researchers have been focused on the study of the chemoprotective and anticancer properties of a variety of antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained solution was then mixed to an H 2 O 2 , 200 mM 1 : 1 (v/v) (Fisher Scientific, USA). This oxidizing solution was used immediately after preparation [ 14 , 20 ].…”
Section: Methodsmentioning
confidence: 99%